Funkcje par wyrazów połączonych relacją konwersywności. Analiza korpusowa na przykładzie par mąż : żona, lekarz : pacjent, nauczyciel : uczeń i kupować : sprzedawać - Mikołajczak-Matyja, Nawoja (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The aim of the paper is to investigate whether pairs of words connected by a semantic relation of converseness perform the same functions in contexts as strong semantic binary oppositions of other types. The following four pairs were analysed: mąż : żona (husband : wife), nauczyciel : uczeń (teacher : student), lekarz : pacjent (doctor : patient) and kupować : sprzedawać (buy : sell). A total of 800 sentences in which members of one of these four pairs co-occur were analysed. The sentences were selected from the National Corpus of Polish. The tool used for the analysis was a set of functions performed by oppositional pairs, used in recent decades in research on various European and non-European languages. In the sets of sentences, for all tested pairs of converses, a significant share of two functions was found: ancillary and coordinated – they were the same ones that had turned out to be the most frequent in previous studies on oppositions of other types. This share was larger for the kupować : sprzedawać pair than for pairs of nous.